ENHANCED PRODUCTION OF EXO-POLYGALACTURONASE FROM AGRO-BASED PRODUCTS BY ASPERGILLUS SOJAE - Ali Oguz Buyukkileci; Canan Tari; Marcelo Fernandez-Lahore (BioResources, 2011)
Aspergillus sojae has been previously shown to produce exo-polygalacturonase (exo-PG) in synthetic media, where the potential of the organism to utilize agricultural substrates was not considered so far. In this study, the utilization of agro-based products was taken into account in the enhanced production of exo-PG using an A. sojae mutant by applying statistical design methods. Complex sources (orange peel, wheat bran, and corn meal), simple sugar sources (glucose, maltrin, and sugar beet syrup), and two phosphate salts were screened using D-optimal design method. Orange peel yielded the highest exo-PG activity with all simple sugars and phosphate sources. According to the results of response surface methodology (RSM), the optimum concentrations of orange peel, sugar beet syrup, and (NH4)2SO4 were found to be 10, 60, and 8 g L-1, respectively. The exo-PG activity under these conditions was 145.4 U m L-1 in shake flask cultures. In bioreactor studies enzyme production was induced at low pH values; thus highest production was obtained under uncontrolled pH conditions, in which the pH dropped to 2.0 in 72 h. As a result high exo-PG could be produced by an A. sojae mutant using a cost-effective medium containing agro-industrial substrates. Another important advantageous outcome was the low optimal pH, which is especially desired in industrial fermentations prone to contamination problems. In fact this highlights the easy adaptation of this fermentation to industrial scales.